Zelig jako docufiction - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
This close-reading analysis and interpretation examines the original form of Woody Allen’s masterpiece Zelig (1983). The author combines a film studies approach with an investigation of epistemological and semiotic reflections on moving images. The author emphasises that more than three decades ago Allen gave to a wide audience a critical, sceptical and ironic vision of the “documentary” (esp. regarding the “truth”) status of moving pictures. This study also introduces also important terminological distinction between “mockumentary” (“fake-documentary”) and a contrasting category, that is, “documentary fiction” (also called “docufiction”), giving an instructive and precise definition of both.